Chemoselective Alteration of Fluorophore Scaffolds as a Strategy for the Development of Ratiometric Chemodosimeters. (20th March 2017) - Zhou, Xinqi; Lesiak, Lauren; Lai, Rui; Beck, Jon R.; Zhao, Jia; Elowsky, Christian G.; Li, Hui; Stains, Cliff I.
Abstract: Ratiometric sensors generally couple binding events or chemical reactions at a distal site to changes in the fluorescence of a core fluorophore scaffold. However, such approaches are often hindered by spectral overlap of the product and reactant species. We provide a strategy to design ratiometric sensors that display dramatic spectral shifts by leveraging the chemoselective reactivity of novel functional groups inserted within fluorophore scaffolds. As a proof‐of‐principle, fluorophores containing a borinate (RF620 ) or silanediol (SiOH2R ) functionality at the bridging position of the xanthene ring system are developed as endogenous H2 O2 sensors. Both these fluorophores display far‐red to near‐infrared excitation and emission prior to reaction. Upon oxidation by H2 O2 both sensors are chemically converted to tetramethylrhodamine, producing significant (≥66 nm) blue‐shifts in excitation and emission maxima. This work provides a new concept for the development of ratiometric probes.